ENSURING ECONOMIC SECURITY OF THE CENTRAL ASIAN REGION (Eureka Journal of Business, Economics & Innovation Studies, 2026)
The provided text analyzes the multifaceted nature of regional economic security within Central Asia, with a specific focus on the Republic of Uzbekistan. It explores the protective mechanisms for individuals and states against internal and external threats, highlighting the importance of socio-economic stability. The study provides a detailed statistical analysis of Uzbekistan's trade turnover with neighboring states (2016–2025), noting a significant 3.3-fold increase in regional trade. Key challenges addressed include the region's heavy reliance on raw material exports, high transport and logistical costs due to being landlocked, and acute environmental threats—specifically water scarcity and uneven resource distribution. The text concludes with strategic recommendations for deepening integration through optimized transit policies, food security cooperation, and economic diversification into high-value-added sectors.
Keywords: Regional economic security, Central Asia, foreign trade turnover, economic integration, water resource management, sustainable development, logistics and transit corridors, diversification, food security, environmental threats.